Study of Bengkuang Mask Formulation (PachyrhizusErosus L) with Ethanol Extract of Sweet Potato Leaves (Ipomoea Batatas L) as Antioxidant - Irma Zarwinda; Azmalina Adriani; Al FhahyalAulia Yunas (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2020)
The leaves of purple sweet potato or purple yam contain compounds that are essential and provide a good benefits for human health such as vitamins, protein, calcium, iron, beta-carotene, and etc. As antioxidant source, it can be added as an active compounds to mask which mostly used in this era. The present study aims to prepare and characterize the mask prepared using bengkuangor Jicama/Mexican turnip as basic mask, combined with an ethanol extract of sweet potato eaves as antioxidant. Mask formulation was made by the experimental method.The face mask formulation was made by mixing three ingredients namely bengkuangpowder, ethanol extract of purple sweet potato and real honey.The organoleptic test, irritation test and preference test (probandus) were used to characterized three as-prepared masks (F1, F2, and F3). The results showed that the liquid (F1) and semi-solid (F2 and F3) masks, ethanol extract of purple sweet potato leaves provides an additional aroma to the as prepared mask in wich the F3 mask has the best aroma compared to the other mask. In irritation testing, no irritation occurred after 2 weeks for the 3 formulas that were made. The subsequent studies are changes in facial skin after wearing a mask for 2 weeks, the face felt every probandus face becomes a little more moist and smoother. Therefore, the face mask type 3 (F3) was the best formulation for considered for further application.